2016
DOI: 10.1155/2016/2869572
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Vascular Endothelial Growth Factor on Bone Morphogenetic Proteins Induced Bone Formation In Vivo: Influencing Factors and Future Research Directions

Abstract: Vascular endothelial growth factor (VEGF) and bone morphogenetic proteins (BMPs), as key mediators in angiogenesis and osteogenesis, are used in a combined delivery manner as a novel strategy in bone tissue engineering. VEGF has the potential to enhance BMPs induced bone formation. Both gene delivery and material-based delivery systems were incorporated in previous studies to investigate the synergistic effects of VEGF and BMPs. However, their results were controversial due to variation of methods incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 111 publications
(157 reference statements)
1
56
0
Order By: Relevance
“…TCTP and VEGF up regulated DSPP expression on day 1 and BMP-2 expression on day 1 and day 3, which supports that both proteins can promote pulp cells differentiation, especially in TCTP/VEGF supplemented in HEMA-treated pulp cells. A recent study revealed that VEGF may have synergist effect to BMPs, including on cell survival and mineralization (23). Further investigation may be required concerning the potential connection of the two mechanisms protecting cell death and differentiation, since both VEGF and TCTP had anticytotoxicity and promoted cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…TCTP and VEGF up regulated DSPP expression on day 1 and BMP-2 expression on day 1 and day 3, which supports that both proteins can promote pulp cells differentiation, especially in TCTP/VEGF supplemented in HEMA-treated pulp cells. A recent study revealed that VEGF may have synergist effect to BMPs, including on cell survival and mineralization (23). Further investigation may be required concerning the potential connection of the two mechanisms protecting cell death and differentiation, since both VEGF and TCTP had anticytotoxicity and promoted cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Blood supply is undoubtedly the absolute goal for any tissue engineering manipulation of the musculoskeletal system and osteonecrotic bone[ 22 , 31 ]. It is well understood that the reconstruction of the local microcirculation is prerequisite for effective bone regeneration[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considerable effort, using in vitro and in vivo models including animal models, has been directed towards understanding the effect of growth factors and transcription factors on bone resorption and formation. Through the last decades it was well established that VEGF is a crucial part of the wide network of the molecules regulating osteoinduction on the femoral head like BMPs, leptin, hypoxia - inducible factor (HIF) and their target genes[ 22 - 25 ]. Under these considerations, an experimental model of cryosurgically-induced ONFH in canines was used to assess the power of our hypothesis that VEGF could be a crucial therapeutic factor for bone tissue remodeling and reversal of osseous degradation during the treatment of ON.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF is highly expressed by endothelial progenitor cells at sites of bone healing and this is thought to be an important mechanism stimulating angiogenesis and facilitate the commencement of bone repair (Hu & Olsen, ). VEFG has been shown to potentiate the bone‐forming capacity of BMPs (Cui, Dighe, & Irvine, ), but these synergistic effects have not been observed consistently (Li, Wang, Qiu, Su, & Wu, ).…”
Section: Biologic Factors In Bone Formation and Regenerationmentioning
confidence: 99%